MOBILEWHEEL A mobile driving station - Cunha, Vitor (2013)
Current mobile devices (e.g., smartphones) are equipped with several sensors that allow different forms of userinteraction. They also offer several connectivity options and a growing computing power which supports itsuse in new Human Computer Interaction (HCI) scenarios. This paper presents the mobileWheel, a system thatexploits the capabilities of current mobile devices as a means of interaction with a real-time graphical drivingsimulation running on a desktop computer. The application on the mobile device performs data acquisitionfrom various sensors (focusing on the 3D accelerometer) and also provides different types of feedback tothe user. This system represents a ubiquitous, simple and affordable alternative approach to the traditionalcontrol of virtual vehicles in driving simulators and could also be applied in other similar architectures. Toevaluate and validate this approach several tests were conducted with volunteer users. The control mode wherethe virtual vehicle is fully controlled by the accelerometer had the highest acceptance and produced the bestresults.